Flexural and Tensile Properties of Different Aluminum Alloy through Simulation Analysis - Muhammad Nizam, Farah Nur Arissa; Syed Abu Bakar, Dr. Sharifah Adzila (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Metal alloy is a combination of pure metal with another material in order to improve its properties. The selection of pure metal and another materials depends on it application. In this research, different aluminum alloy will be used to conduct the simulation. Aluminum alloy was selected in this research because this metal alloy was widely used in industries. Therefore, the objective of this study are to identify the flexural and tensile properties of aluminum alloy with different type of aluminum alloy and to analyse the effect of different load in flexural and tensile testing through simulation analysis. The shape and dimension of sample according to ASTM E8. The samples were designed and analyzed in Solidwork software. The static simulation was selected for flexural and tensile testing. The parameter that obtain in Solidwork simulation is stress, strain and displacement. Moreover, the result of stress and strain was plotted in graph to obtain the flexural and tensile strength of samples. From the result, samples (AA2014, AA2024, AA3003, AA6061 and AA7079) with 5000 N of applied load had the highest value of flexural and tensile strength while samples (AA2014, AA2024, AA3003, AA6061 and AA7079) with 1000 N of applied load had the lowest value of flexural and tensile strength. Thus, the applied load was affected flexural and tensile strength meanwhile the type of aluminum did not affected the properties. There are some recommendation for future work. One of recommendation is validation of Solidwork simulation result by carried out an experiment. By doing experiment, we can compare the result obtain from simulation and the result will more accurate. Lastly, select a proper software for simulation. We must choose the correct software that can provide the output desired result.